2019
DOI: 10.1002/aelm.201900620
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Evaporated Organic/Ag/Organic Multilayer Transparent Conducting Electrode for Flexible Organic Light‐Emitting Diodes

Abstract: flexibility. In recent times, several prototypes of the flexible display based on OLED have been reported. [2][3][4] However, there are still some issues related to the fabrication of flexible OLEDs. Among the main concerns, securing transparent conducting electrode (TCE) with high mechanical flexibility as well as durability and good thermal stability are the most important issue. Generally, widely used TCE, Indiumtin-oxide (ITO) is not suitable for flexible display applications despite high transparency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…This result also shows that the multilayer Ag-TCE can be fabricated with a thinner Ag film and having electrical and optical properties comparable to the ITO electrode. It has been reported that the smooth surface topography of the ultrathin Ag film improves the transmittance by decreasing light scattering at the electrode surface . Also, this Ag-TCE showed better electrical and optical properties for the lower Ag thickness, as compared to the reported electrode structure .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This result also shows that the multilayer Ag-TCE can be fabricated with a thinner Ag film and having electrical and optical properties comparable to the ITO electrode. It has been reported that the smooth surface topography of the ultrathin Ag film improves the transmittance by decreasing light scattering at the electrode surface . Also, this Ag-TCE showed better electrical and optical properties for the lower Ag thickness, as compared to the reported electrode structure .…”
Section: Resultsmentioning
confidence: 74%
“…The bottom HATCN layer prevents Ag agglomeration and forms uniform ultrathin Ag film by providing suitable nucleation sites for the Ag atoms, as shown in Figure S1. It has been reported that the organic wetting/nucleation layer supports to form a smooth ultrathin Ag film by preventing Ag agglomeration and forming coordinate bonds between Ag and nitrogen atoms through sharing unpaired electrons. , Typically, the ultrathin Ag film onto the organic layer can create an issue of Ag agglomeration under high temperature and device-operating conditions . Hence, the consecutive deposition of the capping layer (HATCN) onto the Ag film not only improves the transmittance of the TCE but also supports to stabilize the ultrathin Ag layer under different operating conditions by forming coordinate bonds between the nitrogen and Ag atoms (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Au/Ag/HAT-CN configuration was developed to promote the effective hole injection from the drain electrode. [49] Finally, we successfully fabricated the PTFT-OLED active circuit based on blue emissive dyes. Figure 6 and Figure S33, Supporting Information, depicted the transfer curves and the corresponding optical images of the PTFT-OLED active circuit at a constant source-drain voltage of −50 V and the constant gate voltage of −50 V, which enable the PTFT to exhibit a switch-on state and supplied a current density of ≈0.625 mA cm −2 thus driving the OLED to achieve an electroluminescent brightness exceeding 100 cd cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…These seeds provide dense nucleation centers for metal deposition, and suppress the growth of large metal islands during the PVD process. Such functional seeding materials include metals (Al, [40][41][42] Au, [43] Ag, [44] and Cu [45] ), dielectrics (Ta 2 O 5 , [46] ZnO, [47][48][49] NiO, [50] TeO 2 , [51] Nb 2 O 5 , [52] MoO 3 , [53] and Cs 2 CO 3 [54] ), polymers (polyethyleneimine [PEI], [19,[55][56][57][58] Ormoclear, [59] and photoresist SU-8 [60] ), and organic monolayers (11-mercaptoundecanoic acid [MUA], [48] [3-aminopropyl]-trimethoxysilane: [3mercaptopropyl]-trimethoxysilane [APTMS:MPTMS], [42,61,62] methyl-terminated alucone, [63] and 1,4-bis[2-phenyl-1,10-phenanthrolin-4-yl]benzene [p-bPPhenB] [64] ). For example, Schubert et al enhanced the wetting of deposited Ag films by using high surface energy metal seed materials such as Ca, Al, and Au (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%